The effects of government spending on real exchange rates: Evidence from military spending panel data - Wataru Miyamoto; Viacheslav Sheremirov; Thuy Lan Nguyen (Federal Reserve Bank of Boston, 2016)
Using panel data on military spending for 125 countries, we document new facts about the effects of changes in government purchases on the real exchange rate, consumption, and current accounts in both advanced and developing countries. While an increase in government purchases causes real exchange rates to appreciate and increases consumption significantly in developing countries, it causes real exchange rates to depreciate and decreases consumption in advanced countries. The current account deteriorates in both groups of countries. These findings are not consistent with standard international business-cycle models. We investigate whether the difference between advanced economies and developing countries in the responses of real exchange rates to spending shocks can be explained by alternative hypotheses.
Keywords: E3; F3; F4; 330; military spending; fiscal policy; real exchange rates; twin deficit; risk sharing